A new Wagnerinus (Coleoptera: Curculionidae) from northern Japan: Description including a DNA barcode - Yoshitake, Hiraku; Kato, Toshihide; Jinbo, Utsugi; Ito, Motomi (Zootaxa, 2008)
Wagnerinus frugivorus sp. nov. (Ceutorhynchinae: Ceutorhynchini) is described from Hokkaido, northern Japan, based on morphological and biological characters. Morphologically, this new species closely resembles Wagnerinus carinulatus (Faust) from the Russian Far East and W. costatus (Hustache) from Japan and Korea in having an emarginate anterior margin of the rostrum, sternite VIII diminished to a pair of small sclerites, and longitudinal rows of endophallic sclerites. However, it is distinctive enough to be distinguished from W. carinulatus and W. costatus mainly by the more conspicuous mucrones of mid and hind tibiae, deeper concavities of ventrites I and II, and larger paired prominences of ventrite V. Also, W. frugivorus clearly differs from W. costatus in terms of host plant utilization, the former feeds on the seed capsules of Weigela middendorffiana (Caprifoliaceae) as larvae, while the latter utilizes midge galls on the axillary buds of Weigela species. In addition to general taxonomic information, we provide a 1366-bp fragment of the mitochondrial cytochrome oxidase subunit I gene from the holotype as a DNA barcode of W. frugivorus and discuss the importance of DNA barcoding combined with species descriptions.